Assessment of social media usage for nursing education among nursing students in school of health sciences, Universiti Sains Malaysia - Setia, Marlysa Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Social media usage among nursing students is quite common in this new era. The existence of social media does help nursing students in seeking and sharing knowledge especially in nursing education. A descriptive cross-sectional study was conducted on 299 of respondents recruited. A validated questionnaire was given to all the respondents that fit with the inclusion criteria. Then, the data was analysed using Statistical Package for the Social Sciences (SPSS) software version 26.0. The general objective of the study was to examine the social media usage for nursing education among nursing students in School of Health Sciences, USM. Descriptive statistic was used to describe socio-demographic characteristic, generalities use of the social media, use of social media and attitude towards social media. Pearson’s Chi-Square was used to analyse the association between programme study (Degree and Diploma) and the average time of social media usage 100% of nursing students used social media. The mostly used the types of social media which were YouTube (70.25%), WhatsApp (38.1), others (27.4%) and Instagram (27.1%). The average time of social media usage was more than 3 hours (49.2%). This study also shown there was no association between programme study (Degree and Diploma) and average time of social media usage. In a conclusion, the nursing students (Degree and Diploma) in USM used social media for nursing education purposes.